2011
DOI: 10.1523/jneurosci.4735-10.2011
|View full text |Cite
|
Sign up to set email alerts
|

The Glutamic Acid-Rich Protein Is a Gating Inhibitor of Cyclic Nucleotide-Gated Channels

Abstract: The cyclic nucleotide-gated (CNG) cation channel of rod photoreceptors is a heterotetramer consisting of homologous CNGA1 and CNGB1a subunits. While CNGA1 is indispensable for channel activation, the specific role of CNGB1a in this process has remained elusive. Here, we show that the N-terminal glutamic acid-rich protein (GARP) domain of CNGB1a and soluble GARP2, which corresponds to the proximal portion of the GARP domain, act as autoinhibitory domains that decrease the opening probability of the CNG channel.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 45 publications
0
33
0
Order By: Relevance
“…RDS haploinsufficiency is known to cause severe structural and functional defects alone, 27,43 and recent work has suggested that GARP2 may play a role in regulating rod sensitivity by altering PDE6 activity and cGMP turnover. [9][10][11]44 In addition, our observation that CNGB1 levels were decreased in the presence of excess GARP suggests that CNG channel function or trafficking may be slightly altered in GARP2-Tg animals. Because our CNG antibodies recognize both CNGB1 and GARP, it is not possible to assess CNGB1 alone by immunofluorescence (although the GARP2-TG protein can be visualized by using the c-Myc antibody).…”
Section: Discussionmentioning
confidence: 90%
“…RDS haploinsufficiency is known to cause severe structural and functional defects alone, 27,43 and recent work has suggested that GARP2 may play a role in regulating rod sensitivity by altering PDE6 activity and cGMP turnover. [9][10][11]44 In addition, our observation that CNGB1 levels were decreased in the presence of excess GARP suggests that CNG channel function or trafficking may be slightly altered in GARP2-Tg animals. Because our CNG antibodies recognize both CNGB1 and GARP, it is not possible to assess CNGB1 alone by immunofluorescence (although the GARP2-TG protein can be visualized by using the c-Myc antibody).…”
Section: Discussionmentioning
confidence: 90%
“…Surface Biotinylation-Cell surface proteins were labeled with 0.8 mM non-cell-permeable sulfo-NHS-SS-biotin (Pierce) and precipitated using streptavidin-agarose beads (Pierce) as described (44). Quantitative Western blots were performed on both total and biotinylated surface proteins using NIH ImageJ software.…”
Section: Methodsmentioning
confidence: 99%
“…Soluble GARP proteins and the GARP region of CNGB1a are thought to interact with proteins in the rim of outer segment disc membranes, including phosphodiesterase (26) and peripherin (27). Furthermore, soluble GARP2 and the GARP region intrinsic to CNGB1a can act as gating inhibitors of the rod CNG channel (28). For human CNGA3, four protein isoforms can arise from alternative splicing because of different exon combinations within the 5Ј region of the mRNA encoding the N-terminal cytoplasmic domain of the subunit (24,29).…”
mentioning
confidence: 99%